A Review on Recent Advancements in Unmanned Underwater Vehicle Design - Puzai, N. M.; Ayob, A. F.; Arshad, M. R. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
Recent advancements in miniature hardware technologies pushed the development of unmanned underwater vehicles (UUVs) towards more innovative designs to cater for unique mission definitions. Considering the recent 10 years of work done by various researchers in the literatures, presented in this paper is an overview of several state of the art technologies involved in the development of UUVs. Design studies are presented, whereby divided into various aspects including structure/hull shapes, propulsion, and motion/hydrodynamics. Emphases are given to the selection of shapes/geometry and the materials used. The advantages and the disadvantages of the components were discussed with respect to hydrodynamic forces acting on the UUVs such as resistance, stability, and motion. In terms of propulsion aspects of the UUVs, the discussions are focused on the related components used and the energy supply on-board of the UUVs.